Suburban Development of St Petersburg: comparison of 2 subjects of Federation long-term visions - Leonid Limonov (European Regional Science Association (ERSA), 2014)
The paper is devoted to problems of ensuring balanced and sustainable development of a very specific and important metropolitan region of the Russian Federation ? the region of St Petersburg and surrounding it Leningrad Oblast. St.Petersburg (City) and Leningrad Oblast (Region) are both constituent entities of the Russian Federation and part of North-West Federal District. The City and the Region are connected with each other by thousands of various relationships: historical, cultural, socio-demographic, economic, labor, transport and administrative. For a long period of time, the City and the Region were part of a single administrative-territorial entity and had common governance bodies that applied a common approach to their development. With the collapse of the Soviet Union in late 1991 the system that ensured consistent management of the development of the City and Region was destroyed. However, no system was created that could be used to coordinate the development of the City and the Region. In the last two decades, problems between the City and the Region arise increasingly often, many of which cannot be solved on the basis of agreed positions of both parties. In 2012-2013 both Leningrad Region and St Petersburg developed their long-term vision documents: Leningrad Region ? a Concept of Social and Economic Development till 2025 and St Petersburg ? a Strategy-2030. The paper is considering main provisions of these documents and key problems which needs a coordinated approach: 1) relocation of industrial enterprises from the city centre to the region 2) relocation of the part of logistical and transportation operations from St Petersburg to Leningrad Region 3) development of Greater St Petersburg See Port facilities 4) coordinated development of recreational zones 5) transformation of gardening cooperatives ("sadovodstva") into regular settlements (municipalities) with all necessary infrustructure 6) development and financing a system of suburban public transport 7) environmental issues, including solid waste treatment 8) mass housing construction in the region at the border of St Petersburg etc. On the basis of the analysis of statistics and international best practices recommendations are formulated to improve the efficiency of the governance of the region, paying special attention to St Petersburg Metropolitan Area, which includes a number of municipalities, located in Leningrad Oblast.
Keywords: R11; R12; H77; 330; Regional Development; Metropolitan Area; Environment; Suburban; Inequality; City Size; Inner City; Municipalities; Intergovernmental Relations